2009
DOI: 10.1002/zoo.20254
|View full text |Cite
|
Sign up to set email alerts
|

Thirty years later: enrichment practices for captive mammals

Abstract: Environmental enrichment of captive mammals has been steadily evolving over the past thirty years. For this process to continue, it is first necessary to define current enrichment practices and then identify the factors that limit enhancing the quality and quantity of enrichment, as well as the evaluation of its effectiveness. With the objective of obtaining this information, an international multi-institutional questionnaire survey was conducted with individuals working with zoo-housed mammals. Results of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
133
0
13

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(148 citation statements)
references
References 20 publications
2
133
0
13
Order By: Relevance
“…Several authors have pointed to the value of keeper-conducted behavioral observations but noted the challenges of collecting behavioral data within a daily keeper schedule (Canino & Powell, 2010;Hoy, Murray, & Tribe, 2010a;Margulis & Westhus, 2008;Quirke & O'Riordan, 2013;Shyne, 2006). The 60-min median observation session duration in the studies reviewed here is quite a long period to fit within a keeper's routine.…”
Section: Methods Of Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…Several authors have pointed to the value of keeper-conducted behavioral observations but noted the challenges of collecting behavioral data within a daily keeper schedule (Canino & Powell, 2010;Hoy, Murray, & Tribe, 2010a;Margulis & Westhus, 2008;Quirke & O'Riordan, 2013;Shyne, 2006). The 60-min median observation session duration in the studies reviewed here is quite a long period to fit within a keeper's routine.…”
Section: Methods Of Analysismentioning
confidence: 97%
“…The 60-min median observation session duration in the studies reviewed here is quite a long period to fit within a keeper's routine. Hoy et al (2010a) conducted a survey regarding enrichment for captive mammals; their respondents were 238 professionals from 60 zoos in 13 countries. Respondents reported that while they considered the provision of different kinds of enrichment (e.g., feeding, structural, social, auditory) to be important, only those modalities that were least time-consuming for the staff were frequently provided.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…The most recent movement within animal welfare, and the viewpoint adopted here, focuses on the definition of welfare as the promotion of well-being across three broad aspects: physical health, psychological health, and naturalistic behaviors (Fraser, 2009;Maple, 2007;Swaisgood, 2007). Ultimately, determinations of welfare depend on supporting well-being and require a knowledge of health and physiology, cognition, and social interactions, of animals both in their natural habitat and in managed care (Baumans & Van Loo, 2013;Carlstead, Mench, Meehan, & Brown, 2013;Chua, Weary, Van Delen, & Coenen, 2002;Greenwald & Dabek, 2003;Hoy, Murray, & Tribe, 2010;Kuczaj, Makecha, Trone, Paulos, & Ramos, 2006;Pomerantz & Terkel, 2009;Walker, Diez-Leon, & Mason, 2014;Whitham & Wielebnowski, 2013).…”
Section: The Science Of Animal Well-beingmentioning
confidence: 99%
“…These changes have led to improvements in the welfare of laboratory animals (e.g., mice, rats, guinea pigs, gerbils, rabbits, dogs, cats, non-human primates) and a variety of animals housed at zoos through cognitively and behaviorally enriching activities and changes in their physical environments and social groupings (Baumans & Van Loo, 2013;Hoy et al, 2010;Whitham & Wielebnowski, 2013). For example, by observing the behavioral responses to different enrichments (e.g., devices, social partners, lights, noises, or food), researchers better understand the importance of environmental preferences, species differences, and individual differences when determining the welfare needs of animals in managed care (Baumans & Van Loo, 2013;Chua et al, 2002;Greenwald & Dabek, 2003;Hoy et al, 2010;Pomerantz & Terkel, 2009).…”
Section: The Science Of Animal Well-beingmentioning
confidence: 99%
See 1 more Smart Citation